Proteostasis Regulators Restore Function of Epilepsy-Associated GABAA Receptors. Issue 1 (21st January 2021) - Di, Xiao-Jing; Wang, Ya-Juan; Cotter, Edmund; Wang, Meng; Whittsette, Angela L.; Han, Dong-Yun; Sangwung, Panjamaporn; Brown, Renae; Lynch, Joseph W.; Keramidas, Angelo; Mu, Ting-Wei
Summary: Proteostasis deficiency in mutated ion channels leads to a variety of ion channel diseases that are caused by excessive endoplasmic reticulum-associated degradation (ERAD) and inefficient membrane trafficking. We investigated proteostasis maintenance of γ-aminobutyric acid type A (GABAA ) receptors, the primary mediators of neuronal inhibition in the mammalian central nervous system. We screened a structurally diverse, Food and Drug Administration-approved drug library and identified dinoprost (DNP) and dihydroergocristine (DHEC) as highly efficacious enhancers of surface expression of four epilepsy-causing trafficking-deficient mutant receptors. Furthermore, DNP and DHEC restore whole-cell and synaptic currents by incorporating mutated subunits into functional receptors. Mechanistic studies revealed that both drugs reduce subunit degradation by attenuating the Grp94/Hrd1/Sel1L/VCP-mediated ERAD pathway and enhance the subunit folding by promoting subunit interactions with major GABAA receptors-interacting chaperones, BiP and calnexin. In summary, we report that DNP and DHEC remodel the endoplasmic reticulum proteostasis network to restore the functional surface expression of mutant GABAA receptors. Graphical Abstract: Highlights: DNP and DHEC enhance surface expression of epilepsy-causing mutant GABAA receptors DNP and DHEC restore whole-cell and synaptic currents of mutant GABAA receptors DNP and DHEC reduce ERAD by inhibiting critical ERAD factors for GABAA receptors DNP and DHEC promote folding by enhancing the binding of pro-folding chaperones Abstract : Di et al. demonstrated that proteostasis regulators dinoprost and dihydroergocristine correct the functional surface expression of misfolding-prone GABAA receptors. They function by reducing the ERAD and promoting the productive folding and forward trafficking of mutant receptors.